(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
In the present work the effect of resonant electromagnetic irradiation (EMI) and acetylsalicylic acid (ASA) on value change of the surface tension coefficient of human blood plasma has been studied. It was shown that both the plasma irradiation and the ASA insertion into plasma result in changing of the surface tension coefficient of human blood plasma, as well as affect the surface buffering. These changes are due to the fact that the mentioned factors invoke conformational alterations in the structures of plasma proteins, though we assume that ASA contributes in stabilization of structural changes of proteins.